EFECTO PROTECTOR DE UNA VACUNA POLIVALENTE ANTICLOSTRIDIAL SOBRE LA MORTALIDAD NEONATAL EN ALPACAS. - Rosadio A., Raúl (2012)
This paper analyse the beneficial effect of a multivalent vaccine in reducing mortality rates due to enterotoxemia in alpaca crias. The programme was implemented in 2001 and ran for six consecutive years (2001-2006) in a cooperative farm in southern Peru (Nuñoa, Puno) using a multiple anaculture (bacterine and toxoid) containing predominantly (60%) two subtypes of Clostridium perfringens (A and Aβ2). During these six years, different vaccination protocols were used including inoculating both mothers and crias in the first year and either mothers (2003) or only crias (2002, 2004-2006). The impact of the vaccination was evaluated by comparing total and specific neonatal mortality rates due to enterotoxemia relative to the same rates recorded for the year prior to initiation of the programme (2000). A reduction in total neonatal mortality was recorded from 33.4% in 2000 with no vaccination, to 25.2, 23.7, 9.4, 12.1, 15.1, and 14.3% in years 2001 to 2006. The vaccine equally reduced the mortality associated with enterotoxemia from 19.5% (2000) to 7.2, 9.1, 1.0, 0.3, 2.1, and 3.9% for 2001 through 2006. The polyvalent anaculture (bacterine and toxoid) significantly reduced total mortality rate as well as neonatal mortality rate due to enterotoxemia.